Inequality of Rights in Verstek Divorce: Islamic Law Perspective and Practices in Religious Courts - Ridmajayanti; Alwi Jaya; Arifullah; Jumra; Nurmisari (Journal of Indonesian Scholars for Social Research, 2025)
Verstek divorce rulings, where one party does not attend court proceedings, often result in inequalities in fulfilling the rights of ex-wives. This study explores the legal obligations of husbands toward their former spouses in verstek divorce cases, analyzing both Islamic legal principles and judicial practices in Indonesian Religious Courts. Using an empirical juridical approach, this research was conducted at the Watampone Religious Court Class IA through legal document analysis and interviews with judges and other key stakeholders. The findings indicate that while Islamic law mandates husbands to provide financial support to their ex-wives, including nafkah iddah (maintenance during the waiting period) and nafkah mut’ah (consolation gifts), these provisions are often not enforced effectively in verstek decisions. The absence of the husband in court proceedings significantly affects the judicial process, limiting the court’s ability to ensure compliance. Additionally, many women lack legal awareness, leading to challenges in claiming their rights. Even when courts rule in favor of ex-wives, enforcing financial obligations remains a major issue due to weak legal execution mechanisms. This study highlights the urgent need for improved legal frameworks and enforcement strategies to protect women’s rights in verstek divorce cases. Strengthening legal aid services, increasing judicial oversight, and enhancing post-divorce monitoring mechanisms are essential steps to ensure the equitable implementation of Islamic family law.